(untitled) (Ecological Bulletin of Kryvyi Rih District, 2024)
The study of the taxonomic composition of the native flora of Kryvyi Rih allowed to register 740 species of angiosperms, representing 335 genera of 79 families. The species of the class Magnoliopsida significantly prevail in terms of numbers, which include 594 species of 273 genera of 60 families. Monocots - Liliopsida include 146 species of 62 genera of 19 families. The study of the taxonomic composition of the native flora of Kryvyi Rih allowed us to identify 234 species of medicinal plants of 146 genera of 55 families. During the analysis of the taxonomic composition of medicinal plants of the native flora, the largest number of species and genera was found, which include the following 30 families Lamiaceae – 26 / 16; Asteraceae – 26 / 14; Caryophyllaceae – 16 / 10; Scrophulariaceae – 15 / 5; Rosaceae – 14 / 11; Ranunculaceae – 14 / 8; Polygonaceae – 14 / 4; Fabaceae – 8 / 7; Chenopodiaceae – 7 / 6; Plantaginaceae – 7 / 1; Brassicaceae – 6 / 6; Apiaceae – 6 / 5; Rubiaceae – 5 / 1; Poaceae – 4 / 3; Dipsacaceae – 4 / 3; Boraginaceae – 3 / 3; Crassulaceae – 3 / 3; Valerianaceae – 3 / 2; Lemnaceae – 3 / 2; Campanulaceae – 3 / 1; Ulmaceae – 3 / 1; Gentianaceae – 3 / 1; Salicaceae – 2 / 1; Limoniaceae – 2 / 1; Primulaceae – 2 / 1; Urticaceae – 2 / 1; Convolvulaceae – 2 / 1; Cuscutaceae – 2 / 1; Clusiaceae – 2 / 1; Convallariaceae –2 / 1. 25 families contain only 1 species of 1 genus.